'Queer Italian migrations': Tonino De Bernardi's Rosatigre (Tiger Rose) (2000) and the reconfiguring of Roberto Rossellini's Stromboli, terra di Dio (Stromboli, Land of God) (1950). Issue 1 (1st January 2018) - Brett, Oliver
The documentary film focusing on queer identities in post-Millennial Italy reveals interesting key features, including the often intense collaboration of filmmakers and their subjects, the hybridity of genre and interrogation of those representations and identities being explored, and the increased agency and performance of participants. While, respectively, requiring further research, these features reflect what appears to be a propensity towards the 'intertextual'. I approach this aspect here through Tonino De Bernardi's sensory challenging 'docu-fiction' film Rosatigre (Tiger Rose) in 2000, which exploits, alongside the more general conventions of cinema, Roberto Rossellini's Stromboli, terra di Dio (Stromboli, Land of God) in 1950. Positioned in relation to a corpus of other texts, I consider how these two films explore the issue of 'migration' beyond fixed categories. In talking of queers who migrate but also of queering migration, an interconnection of various narratives can be seen to broaden our understanding of the migrant figure in the Italian context.